Zimna fakoemulsyfikacja w operacjach łączonych fakoemulsyfikacji oraz witrektomii - Nawrocki, Jerzy; Michalewska, Zofia; Michalewski, Janusz; Cisiecki, Sławomir (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: The aim of this paper is to present the use of bimanual phacoemulsification technique in combined phacoemulsification and vitrectomy surgery. Material and methods: Combined phacoemulsification and vitrectomy procedure was performed in 20 eyes. Phacoemulsification was performed through two paracenteses. Soft acrylic intraocular lenses were implanted into the capsular bag through a paracentesis 1.8 mm wide. Standard three-port pars plana vitrectomy followed. Indications for vitrectomy were diabetic retinopathy, retina detachment, uveitis, macula hole. All surgeries were performed as one-day surgeries. Follow-up lasted six months. Results: Visual acuity improved in 19/20 eyes (95%). The achieved functional results were similar to that achieved in standard phacoemulsification combined with vitreoretinal surgery. Surgery time did not differ significantly from time needed to perform a standard procedure. The bimanual technique allowed the stablization of the anterior chamber during vitreoretinal surgery. No serious postoperative complications occurred. Conclusions: The presented method improves the quality of combined surgery, ensures stability of the anterior chamber, reduces postoperative astigmatism, lowers the risk of inflammation.